2014
DOI: 10.3906/bot-1405-29
|View full text |Cite
|
Sign up to set email alerts
|

The molecular characterization and expression analyses of ethylene receptor genes from watermelon fruit

Abstract: Watermelon fruit is very sensitive to ethylene, showing rapid deterioration and water-soaking upon ethylene exposure. The objective of this study was to isolate and determine the expressions of ethylene receptor genes in watermelon fruit. As a result of PCR amplification of cDNAs obtained via RT-PCR of total RNA from watermelon fruit with degenerate primers, 3 partial cDNAs were obtained. After extension of the 3' and 5' ends of the cDNAs via 3' and 5' RACE analysis, 3 full-length genes designated as CL-ETR1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Thus, applying a systematic identification and functional study of these stress responsive genes is necessary to elucidate the molecular mechanisms of tolerance and susceptibility in Cucurbitaceae crops (e.g., cucumber and watermelon). So far, few TCS genes have been characterized in Cucurbitaceae crops (Yamasaki et al, 2000 ; Karakurt et al, 2014 ). Three ethylene receptors in cucumber belonged to HK(L) family, have been proved to participate in the formation and development of female flower (Yamasaki et al, 2000 , 2003 ; Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, applying a systematic identification and functional study of these stress responsive genes is necessary to elucidate the molecular mechanisms of tolerance and susceptibility in Cucurbitaceae crops (e.g., cucumber and watermelon). So far, few TCS genes have been characterized in Cucurbitaceae crops (Yamasaki et al, 2000 ; Karakurt et al, 2014 ). Three ethylene receptors in cucumber belonged to HK(L) family, have been proved to participate in the formation and development of female flower (Yamasaki et al, 2000 , 2003 ; Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li, Qiao, Tong, Zhou, and Zhang () showed that 1‐MCP upregulated the expression of the ETR3 gene in pear fruit 0 d–9 d after harvest and downregulated the expression of ERS2 6 d–15 d after harvest. Karakurt, Tonguç, and Ünlü () confirmed that 1‐MCP markedly decreased the expression levels of the ETR1 , ERS1 , and ETR2 genes in watermelons. Moreover, 1‐MCP has been broadly used to delay ripening and senescence in plants and to consequently extend the storage life of climacteric fruit.…”
Section: Introductionmentioning
confidence: 88%
“…Non-climacteric fruits express many ethylene biosynthesis genes as well as a series of ethylene signaling components, such as ethylene receptors (ETRs), the negative regulator constitutive triple response (CTR1), and the transduction factors ethylene insensitive 2 (EIN2) and ethylene insensitive 3 (EIN3), EIN3-like (EIL), and ethyleneresponsive factor (ERF) (Osorio et al, 2012). Expression of these important signal transduction elements is upregulated to varying degrees during the ripening and softening processes of nonclimacteric fruits, as observed in strawberry (Trainotti et al, 2005;Sun et al, 2013;Qian et al, 2016), grape (Chervin and Deluc, 2010;Muñoz-Robredo et al, 2013;Qian et al, 2016;Ye et al, 2017), orange (Katz et al, 2004;Distefano et al, 2009;Wu et al, 2016;Kashyap and Banu, 2019), loquat (Aloś et al, 2017), cherry (Ren et al, 2011;Xanthopoulou et al, 2022), and watermelon (Karakurt and Huber, 2008;Karakurt et al, 2014). These findings indicate that ethylene indeed plays a critical role in regulating the ripening of nonclimacteric fruits.…”
Section: Introductionmentioning
confidence: 99%